Days of wine and roses - Mancini, Henry 1924-1994 (Warner Bros. Entertainment Inc., 2004)
"Ehe und Karriere eines Public-Relations-Managers werden durch übermäßigen Alkoholkonsum zugrunde gerichtet. [...]" [filmdienst.de]
Original: USA 1962
Bildformat 1.85:1 widescreen
special features: commentary by director Blake Edwards ; vintage Jack Lemmon interview ; theatrical trailer
Keywords: Alcoholics -- Drama.; Feature films.; Alkoholiker; Film; DVD-Video